2023
DOI: 10.1007/s42452-023-05339-2
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Multi-stage biomedical feature selection extraction algorithm for cancer detection

Abstract: Cancer is a significant cause of death worldwide. Early cancer detection is greatly aided by machine learning and artificial intelligence (AI) to gene microarray data sets (microarray data). Despite this, there is a significant discrepancy between the number of gene features in the microarray data set and the number of samples. Because of this, it is crucial to identify markers for gene array data. Existing feature selection algorithms, however, generally use long-standing, are limited to single-condition feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In this study, we used multi-stage feature extraction and classification pipelines with a random forest classifier to predict the kidney function at the biopsy and 1-year prediction, respectively. In general, multi-stage feature extraction and classification pipelines have high predictive accuracy compared to the end-to-end learning which requires a huge amount of data to obtain a high accuracy 42 , 43 . Further, Random Forest classifier is a commonly used machine learning algorithm which provides a higher level of accuracy in predicting outcomes over the decision tree algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we used multi-stage feature extraction and classification pipelines with a random forest classifier to predict the kidney function at the biopsy and 1-year prediction, respectively. In general, multi-stage feature extraction and classification pipelines have high predictive accuracy compared to the end-to-end learning which requires a huge amount of data to obtain a high accuracy 42 , 43 . Further, Random Forest classifier is a commonly used machine learning algorithm which provides a higher level of accuracy in predicting outcomes over the decision tree algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…This is similar to the filter-wrapper and embedded technique utilized for gene expression data in [12]. However, Keshta et al [19] proposed a multi-stage algorithm for the extraction and selection of features in a cancer detection study. It was reported that despite the reduction in the number of features used for classification, the performance of classifiers was either enhanced or unchanged.…”
Section: Introductionmentioning
confidence: 99%